PELAKSANAAN TANGGUNG JAWAB PELAKU USAHA DEPOT ISI ULANG AIR MINUM TERHADAP SERTIFIKAT HALAL DIKAITKAN DENGAN PERLINDUNGAN KONSUMEN (STUDI PENELITIAN DI KECAMATAN MEUREUBO KABUPATEN ACEH BARAT - Moflida, Nina; Sandela, Ilka; Yuana, Adella (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2024)
Article 4 of Law of the Republic of Indonesia Number 33 of 2014 concerning Halal Product Guarantee states that "Products that enter, circulate, and are traded in the territory of Indonesia must obtain a halal certificate". However, in reality in the field there are still many products circulating in the territory of Indonesia that do not have halal certificates and do not apply these rules, especially in Drinking Water Depots in Meurebo District, West Aceh. The purpose of this study is, to determine the responsibility of Drinking Water Refill Depot business actors for the obligation of halal certificates in Meureubo District, West Aceh Regency. To find out the obstacles faced by Drinking Water Refill Depot business actors in carrying out halal certificate obligations. This research uses empirical juridical research methods, which is one type of legal research that analyzes and examines the operation of law in society. The results showed that drinking water refill depot business actors have not been responsible for the halalness of the products produced, because they do not yet have a halal certificate, the business actors believe that the water produced is halal because it has been laboratory tested by the West Aceh Health Office. Obstacles for drinking water refill depot business actors in carrying out halal certificate obligations are the lack of legal awareness of the community, and the lack of public knowledge. Consumers do not get protection in consuming refill drinking water, because business actors do not carry out obligations for halal certificates.